Integration of PjBL Models with Inclusive Teaching Styles To Improve Underhand Service Volleyball Skills - Muhammad Yudhi Ardinnata; Mashud; Herita Warni (Indonesian Journal of Physical Education and Sport Science)
Study purpose. This study aims to prove that the integration of the PjBL models with the inclusive teaching style can improve the underhand service volleyball skills.